EFFECT OF FARMLAND SURFACE COVERED POROUS MULCH MATERIALS ON SOIL WATER, HEAT AND WATER USE EFFICIENCY OF MAIZE - L. S. Feng; Z. X. Sun; C.R. Yan; M. Z. Zheng; J. M. Zheng; N. Yang; W. Bai; C. Feng (Journal of Animal and Plant Sciences, 2015)
surface covered with ordinary mulch increases runoff in the presence of precipitation, leading to limited application. However, using a porous membrane to cover surfaces can solve the problem of rainfall infiltration. In order to study the impact of using porous mulch to allow soil water heat to be utilized in a more efficient manner, we have carried out this study. We have found that porous mulch warms the surfaces and allows for water retention during the early stages of maize growth. During the middle and late stages of maize growth, the mulch cooled the surface. The moisture of the soil when covered by porous mulch was uniformly distributed during the dry season, when ordinary mulch would cause soil desiccation. Water utilization efficiency of crop that covered porous mulch respectively increased by 0.37kg/m3 , 0.45kg/m3 , 0.81kg/m3 than that of covered the ordinary mulch, covered straw or the bare land in respectively
Keywords: Maize; Porous Mulch; Soil Moisture; Soil Temperature; Water Utilization Efficiency